CO2 electroreduction on bimetallic Pd–In nanoparticles. Issue 13 (23rd June 2020) - Pavesi, Davide; Ali, Farhan S. M.; Anastasiadou, Dimitra; Kallio, Tanja; Figueiredo, Marta; Gruter, Gert-Jan M.; Koper, Marc T. M.; Schouten, Klaas Jan P.
Abstract : The interaction of In and Pd in bimetallic particles causes dramatic changes in the CO2 reduction behavior. Abstract : CO2 electroreduction powered by renewable energy is an attractive strategy to recycle air-based carbon. One of the current challenges for the scale up of the technology is that the catalysts that show high faradaic yield at high current density (post-transitional metals such as In, Sn, Bi, Pb) suffer from very high overpotentials of more than 1 V. On the other hand, Pd can convert CO2 to formate with almost no overpotential, but is readily poisoned by CO and deactivates when trying to reach industrially relevant currents. In this work we show the effect of the interaction of In and Pd in bimetallic nanoparticles, reaching the conclusion that this interaction causes a loss of selectivity towards formate and at the same time suppresses CO poisoning of Pd sites. The results of the catalyst characterization suggest the formation of intermetallic PdIn compounds that in turn cause the aforementioned behavior. Based on these results, it seems that geometric and electronic effects in Pd based intermetallic compounds can alleviate CO poisoning on Pd sites. In the case of PdIn intermetallics this leads to the loss of CO2 reduction activity, but this strategy may be useful for other electrochemical reactions that suffer from the same problem of deactivation. It remains to be seen if intermetallic compounds of Pd with other elements can yield viable CO2 reduction catalysts.